Cryptic Lives of Conspicuous Animals: Otolith Chemistry Chronicles Life Histories of Coastal Lagoon Fishes - Feyrer, Frederick; Young, Matthew; Fong, Darren; Limburg, Karin; Johnson, Rachel (Frontiers in Marine Science, 2020)
Bar-built coastal lagoons are dynamic ecosystems at the land-sea interface that are important habitats for a variety of species. This study examined the habitat ecology of two lagoon species, the imperiled Tidewater Goby (Eucyclogobius newberryi) and the Prickly Sculpin (Cottus asper) by reconstructing individual life histories from patterns in the concentration of the element Sr (as ratioed to Ca; Sr:Ca) in otoliths. Specific objectives were to (1) elucidate any movements of individual fishes among three primary habitat components of typical bar-built lagoon systems: coastal ocean, brackish lagoon, and freshwater watershed streams, and (2) determine if either species exhibited a consistent life history as defined by a stereotypical otolith Sr:Ca chronology, which could be indicative of a consistent range of salinity or temperature occupied through ontogeny. Results indicated that Tidewater Goby was a lagoon resident and that Prickly Sculpin exhibited migrations between lagoon and watershed stream habitats. There was no strong evidence in either species of ocean occupancy or of a stereotypical Sr:Ca chronology, the latter suggesting the full range of available lagoon habitat in terms of salinity and temperature was likely utilized at all life stages. These findings add to the body of evidence that bar-built lagoons are not isolated habitats and should be managed holistically with adjoining watershed and marine environments to ensure habitat connectivity across the landscape.